Modeling of microscale transport in biological processes - Becker, Sid M. (Amsterdam Academic Press is an imprint of Elsevier, 2017)
Modeling of Microscale Transport in Biological Processes provides a compendium of recent advances in theoretical and computational modeling of biotransport phenomena at the microscale. The simulation strategies presented range from molecular to continuum models and consider both numerical and exact solution method approaches to coupled systems of equations. The biological processes covered in this book include digestion, molecular transport, microbial swimming, cilia mediated flow, microscale heat transfer, micro-vascular flow, vesicle dynamics, transport through bio-films and bio-membranes, and microscale growth dynamics. The book is written for an advanced academic research audience in the fields of engineering (encompassing biomedical, chemical, biological, mechanical, and electrical), biology and mathematics. Although written for, and by, expert researchers, each chapter provides a strong introductory section to ensure accessibility to readers at all levels.--Provided by publisher.
Chapter 1 - Molecular Simulations of Complex Membrane Models -- Chapter 2 - Microbial Strategies for Oil Biodegradation -- Chapter 3 - Modeling and Measurement of Biomolecular Transport and Sensing in Microfluidic Cell Culture and Analysis Systems -- Chapter 4 - Coupling Microscale Transport and Tissue Mechanics: Modeling Strategies for Arterial Multiphysics -- Chapter 5 - Modeling Cystic Fibrosis and Mucociliary Clearance -- Chapter 6 - Intracellular Microfluid Transportation in Fast Growing Pollen Tubes -- Chapter 7 - Microorganisms and Their Response to Stimuli -- Chapter 8 - Nano-Swimmers in Lipid-Bilayer Membranes -- Chapter 9 - Phase Field Modeling of Inhomogeneous Biomembranes in Flow -- Chapter 10 - Modeling and Experimental Analysis of Thermal Therapy during Short Pulse Laser Irradiation -- Chapter 11 - Micro-Scale Bio-Heat Diffusion Using Green's Functions -- Chapter 12 - Microstructural Influences on Growth and Transport in Biological Tissue—A Multiscale Description -- Chapter 13 - How Dense Core Vesicles Are Delivered to Axon Terminals – A Review of Modeling Approaches -- Chapter 14 - Modeling of Food Digestion -- Index.
Includes bibliographical references and index.
Keywords: Biological transport -- Mathematical models; Transport theory -- Mathematical models; Biological Transport; Models, Theoretical; Electronic books